Beyond the building blocks: integrating community roles into health systems frameworks to achieve health for all. (22nd June 2019) - Sacks, Emma; Morrow, Melanie; Story, William T; Shelley, Katharine D; Shanklin, D; Rahimtoola, Minal; Rosales, Alfonso; Ibe, Ochiawunma; Sarriot, Eric
Abstract : Achieving ambitious health goals—from the Every Woman Every Child strategy to the health targets of the sustainable development goals to the renewed promise of Alma-Ata of 'health for all'—necessitates strong, functional and inclusive health systems. Improving and sustaining community health is integral to overall health systems strengthening efforts. However, while health systems and community health are conceptually and operationally related, the guidance informing health systems policymakers and financiers—particularly the well-known WHO 'building blocks' framework—only indirectly addresses the foundational elements necessary for effective community health. Although community-inclusive and community-led strategies may be more difficult, complex, and require more widespread resources than facility-based strategies, their exclusion from health systems frameworks leads to insufficient attention to elements that need ex-ante efforts and investments to set community health effectively within systems. This paper suggests an expansion of the WHO building blocks, starting with the recognition of the essential determinants of the production of health. It presents an expanded framework that articulates the need for dedicated human resources and quality services at the community level; it places strategies for organising and mobilising social resources in communities in the context of systems for health; it situates health information as one ingredient of a larger block dedicated to information, learning and accountability; and it recognises societal partnerships as critical links to the public health sector. This framework makes explicit the oft-neglected investment needs for community health and aims to inform efforts to situate community health within national health systems and global guidance to achieve health for all.